Dental biofilm serves as an ecological reservoir of acidogenic pathobionts in head and neck cancer patients with radiotherapy-related caries - Julia S. Bruno; Vitor Heidrich; Felipe C. F. Restini; Tatiana M. M. T. Alves; Wanessa Miranda-Silva; Franciele H. Knebel; Elisangela M. Cóser; Lilian T. Inoue; Paula F. Asprino; Anamaria A. Camargo; Eduardo R. Fregnani (mSphere)
ABSTRACT Radiotherapy-related caries (RRC) is an aggressive and debilitating oral toxicity that affects half of the patients who undergo radiotherapy for head and neck cancer. However, the etiology of RRC is not fully established, and there are no clinically validated methods for preventing it. To gain a better understanding of the risk factors and the microbiome’s role in causing RRC, we compared clinicopathological characteristics, oncological treatment regimens, oral health condition, and the oral microbiota at three different oral sites of radiotherapy-treated patients with (RRC+) and without radiotherapy-related caries (RRC−). We observed no significant differences between these groups in the clinicopathological characteristics and treatment regimens. However, RRC+ patients were older and had poorer oral health conditions at the start of the radiotherapy treatment, with a lower number of teeth and a higher proportion of rehabilitated teeth. RRC+ patients had lower microbiota diversity and the dental biofilm of RRC+ patients displayed striking alterations in microbiome composition compared to RRC− patients, including enrichment of acidogenic species and altered metabolic potential, with a higher abundance of genes linked to energy-related pathways associated with the synthesis of amino acids and sugars. We also compared the microbiota of RRC+ tissue with conventional caries tissue, revealing lower bacterial diversity and enrichment of Lactobacillaceae members in RRC+. The insights into the irradiated oral microbiota enhance the understanding of RRC etiology and highlight the potential for microbial-targeted therapies in its prevention and treatment.IMPORTANCEThis study focuses on a dedicated collection of diverse oral sites to comprehensively investigate microbial differences between patients who develop RRC and those who do not. RRC is a severe oral disease that profoundly impacts on the oral health and overall quality of life of cancer survivors. Leveraging shotgun metagenomics, we characterize the unique microbial variations in in vivo irradiated dental biofilms, unveiling novel insights into the microbial ecology of radiotherapy-treated patients. Furthermore, this research integrates extensive data on oral health and oncological profiles, providing a comprehensive understanding of the intricate relationship between oral microbial communities and the outcomes of radiotherapy-induced toxicity.